AKTIVITAS REPELEN EKSTRAK ETANOL DAUN SIRIH MERAH (Piper ornatum) TERHADAP NYAMUK Aedes aegypti - Bangsawan, Bucek Ibrahim; Joharman, Joharman; Widyamala, Erida (Universitas Lambung Mangkurat, 2024)
Abstract: The red betel leaf (Piper ornatum) contains secondary metabolites such as flavonoids, alkaloids, and tannins, which hold potential as repellents. This study aims to examine the repellent activity of the red betel leaf extract (Piper ornatum) against Aedes aegypti mosquitoes. The research design is a true experimental post-test only with a control group, comprising six treatments: extract concentrations of 12.5%, 25%, 50%, and 100%, a negative control (aquadest), and a positive control (DEET 15%). Treatments are applied to the lower arm of the subjects and exposed to mosquitoes for 5 minutes at 0, 60, 120, 180, and 240 minutes. The Shapiro-Wilk and Levene's tests at minutes 0, 60, 120, and 240 showed that the data were not normally distributed and not homogeneous, while at minute 180, the data were normally distributed. Subsequently, the One-Way ANOVA and Kruskall Wallis tests resulted in a p-value of <0.05, suggesting significant differences among treatments. The research findings indicate that at a concentration of 100%, the red betel leaf extract exhibits a repellent efficacy of ≥90% at 0, 60, 120, and 180 minutes. Thus, the red betel leaf extract demonstrates repellent activity at each minute of testing. Keywords: Piper ornatum, red betel leaf, repellent, Aedes aegypti Abstrak: Sirih merah (Piper ornatum) memiliki metabolit sekunder seperti flavonoid, alkaloid, dan tanin yang berpotensi sebagai repelen. Tujuan penelitian ini untuk menganalisis aktivitas repelen ekstrak daun sirih merah (Piper ornatum) terhadap nyamuk Aedes aegypti. Desain penelitiannya adalah eksperimen dengan pascates saja dan kelompok kontrol dengan enam perlakuan yaitu konsentrasi ekstrak 12,5%, 25%, 50%, 100%, kontrol negatif (aquades), dan kontrol positif (DEET 15%). Perlakuan dioleskan pada lengan bawah probandus, dipaparkan selama 5 menit pada nyamuk dimenit ke-0, 60, 120, 180, dan 240. Pada Shapiro-Wilk dan Levene’s dimenit 0, 60, 120, 240 data tidak terdistribusi normal dan homogen, sedangkan menit ke-180 data terdistribusi normal. kemudian pada One-Way ANOVA dan Kruskall Wallis didapatkan nilai p<0,05 yang disimpulkan terdapat perbedaan signifikan. Hasil penelitian menunjukkan pada konsentrasi 100% memiliki persentase daya tolak ≥90% dimenit pengujian dan ekstrak sirih merah memiliki aktivitas repelen di setiap menit pengujian. Kata-kata kunci: Repelen Piper ornatum, daun sirih merah, Aedes aegypti